Intrahousehold allocations by mothers to children: The role of observability - Debosree Banerjee; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2018)
In this article we analyse the impact of spousal preference expectations on mothers' willingness to invest in children's food/nutrition and health/medical expenses. We use a survey conducted in Karnataka, South India, where women with children were asked to state their investment preference in child food and health corresponding to three endowment levels. Alongside, we also attempted to derive their expectations about spousal relative investment choices. We find that if mothers are able to elicit expectations about spousal preference, their own preferences remain unaffected, whereas, if expectation elicitation is impossible, female investments in children reduce significantly. We argue that in the absence of information sharing, uncertainty is created which decreases cooperation by mothers by reducing their willingness to invest in children, especially in girls and increasing their precautionary savings. These results remain consistent across the all endowments. Our study is particularly of relevance for policies that aim to alleviate poverty and improve child human capital accumulation with cash transfer policies. It also suggests that in a noncooperative set up, where household members do not share their financial information, resources tend to be under-allocated in household public goods such as children.
Keywords: D13; D81; D82; J12; 330; Incomplete information; Uncertainty; Noncooperation; Intrahousehold allocation